DARI INSPIRASI HINGGA APRESIASI - Hernawan, Hernawan (Institut Seni Budaya Indonesia Bandung, 2018)
Although the birth of film art is the youngest form of art, but in its work has shaken the world by seizing a spectacular position. When film is recognized as a work of art, film also has the potential for communication that can deliver messages uniquely, so that it can be said as a manifestation of the representation of the lives of its people. However, how can the film be appreciated by the audience? Of course the stages of the process must go a long way starting from the inspiration to the embodiment of appreciation. There are several stages in the process, namely the stage of idea finding, development, packaging and formation until tangible to be appreciated. The idea-seeking stage is the stage of absorption of inspiration stimulated by aesthetic experiences. The development phase is to motivate the theme and the problems to be expressed in its realization. After that it is then packaged based on literary rules into a scenario. Furthermore, the interpretation of the manuscript is done to form through several components of creative workers. Compiled based on cinematic elements to the form of film packaging that can be appreciated.